The contribution of circadian clock to the biological processes - Luo, Beibei; Song, Jiangyuan; Zhang, Jiaqi; Han, Jun; Zhou, Xin; Chen, Lili (Frontiers in Molecular Biosciences, 2024)
All organisms have various circadian, behavioral, and physiological 24-h periodic rhythms, which are controlled by the circadian clock. The circadian clock controls various behavioral and physiological rhythms. In mammals, the primary circadian clock is present in the suprachiasmatic nucleus of the hypothalamus. The rhythm of the circadian clock is controlled by the interaction between negative and positive feedback loops, consisting of crucial clock regulators (including Bmal1 and Clock), three cycles (mPer1, mPer2, and mPer3), and two cryptochromes (Cry1 and Cry2). The development of early mammalian embryos is an ordered and complex biological process that includes stages from fertilized eggs to blastocysts and undergoes important morphological changes, such as blastocyst formation, cell multiplication, and compaction. The circadian clock affects the onset and timing of embryonic development. The circadian clock affects many biological processes, including eating time, immune function, sleep, energy metabolism, and endocrinology，therefore, it is also crucial for overall health, growth and development after birth. This review summarized the effects of the circadian clock in the body's physiological activities. A new strategy is proposed for the prevention of malformations or diseases by regulating the circadian clock or changing circadian rhythms.